(untitled) (Italiano LinguaDue, 2021)
The development, support and recognition of plurilingual competence, in other words a person´s ability to perform successfully in a plurilingual setting, required school curricula to include not only the instruction of at least two foreign languages (e.g. Italian and English as foreign languages) within one course but also a corresponding exam format. We will outline the guidelines for and challenges of a plurilingual syllabus, explore the concepts of bilingualism, plurilingualism and multilingualism and give clear examples of what we believe an oral plurilingual examination should look like. Guidelines for teachers on how to develop competence-oriented plurilingual tasks will also be accompanied by the necessary test specifications. In addition, 14 possible situations for examinations are provided. An assessment grid and examples of test papers complete the document on bilingual competences and their simultaneous evaluation in two foreign languages. Dall’insegnamento plurilingue all’esame plurilingue Lo sviluppo, il supporto e il riconoscimento della competenza plurilingue, in altre parole della capacità di una persona di muoversi con successo in un ambiente plurilingue, ha richiesto che i programmi scolastici includessero non solo l’insegnamento di almeno due lingue straniere (ad es. italiano e inglese come lingue straniere) all’interno del curricolo di studi, ma anche un corrispondente formato d’esame. In questo contributo descriveremo le linee guida e le sfide di un programma plurilingue, esploreremo i concetti di bilinguismo, plurilinguismo e multilinguismo e forniremo esempi chiari di come crediamo che dovrebbe essere un esame plurilingue orale. Le linee guida per gli insegnanti su come sviluppare compiti plurilinguistici orientati alle competenze saranno inoltre accompagnate dalle necessarie specifiche indicazioni per l’esame. Inoltre, sono previste 14 possibili situazioni per gli esami. Una griglia di valutazione ed esempi di prove d’esame completano il documento sulle competenze bilingui e la loro valutazione simultanea in due lingue straniere.